(untitled) (MAUSAM, 1958)
The occurrence of thunderstorms in the pre-monsoon season over Gangetic West Bengal in relation to low level synoptic conditions as well as high level perturbations has been examined. It is shown that neither of these factors by itself can produce convective activity, the important condition being the super-position of upper divergence associated with a high level perturbation over a low level convergent area. The upper divergence occurs due to a variety of perturbations-a straight jet stream, a jet stream trough, a trough or even an anti cyclonic vortex and the lower convergence is provided by low or trough at the surface. The importance of sheanng advection in producing divergence ill Jet stream zone is pointed out and the relative efficacy of the various perturbations in producing squalls associated with thunderstorms is analysed.